Youth of the Ukrainian borderland in the transition to the knowledge society: values, educational plans, visions of life success = Młodzież ukraińskiego pogranicza w okresie przejścia do społeczeństwa wiedzy: wartości, plany edukacyjne, wizje sukcesu życiowego - Sokuryanska, Ludmila G.; Shchudlo, Svitlana (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The aim of the study is to provide a comparative analysis of educational plans and values of young people in the Central and Eastern European Borderlands. The authors pay particular attention to the role of education in creating life strategies among secondary school graduates of Ukraine, Poland and Hungary. The empirical basis of the analysis was created based on the results of the international sociological project "Youth in the Borderlines of Central and Eastern Europe".
Keywords: education; values; educational plans; youth; borderland; knowledge society; edukacja; wartości; plany edukacyjne; młodzież; pogranicze; społeczeństwo